Administrative Skills of Small School Administrators Affecting Being a Happy Organization under Samut Songkhram Primary Educational Service Area Office - Paewbanjong, Jirapa; Namawiroj, Panot (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were 1) to study the administrative skills of small school administrators, 2) to study being a happy organization, and 3) the administrative skills of small school administrators affecting being a happy organization under Samut Songkhram Primary Educational Service Area Office. This research was quantitative research. The sample consisted of 139 teachers in small schools under Samut Songkhram Primary Educational Service Area Office, were obtained by using a stratified random sampling according to educational zones and systematic random sampling. The research instrument was a questionnaire with content validity, IOC values between .67-1.00, and a reliability value of .98. The data were analyzed by using frequency, percentage, mean, standard deviation, Pearson correlation coefficient and multiple regression analysis. The research results were found that: 1)the administrative skills of small school administrators was a high level, ranking from the highest to the lowest mean: educational skills, human skills, communication skills, technical skills, conceptual skills, and diagnostic skills. 2) being a happy organization were high level, ranking from the highest to the lowest mean: happy heart, happy soul, happy brain, happy society, happy family, happy money, happy relax, and happy body. 3) the administrative skill of small school administrators affecting being a happy organization were technical skill and human skill, with predictive power of 71.10% and a statistically significant at 0.1 level.